Analisis Penerapan Model Project Based Learning Pada Materi Bangun Datar Mata Pelajaran Matematika Kelas IV - Fitria, Anisa; Azizah, Mira; Suharno, Suharno; Roshayanti, Fenny (LPPM Institut Pendidikan Nusantara Global, 2024)
The aim of this research is to determine the results of applying learning material about flat shapes in Mathematics for class IV students using the Project Based Learning (PjBL) model. The method used in this research uses descriptive qualitative methods. In its implementation, it uses interview guidelines and observation sheets to see the learning process in class IVB. The research sample was all 28 class IVB students. The results of this research indicate that the Project Based Learning (PjBL) learning model is appropriate to be applied in flat shape material in Mathematics subjects. It can be concluded that the Project Based Learning (PjBL) learning model can increase students' creativity. The PjBL learning model is an alternative that teachers can use in learning to train students to learn using project assignments, so that students can design projects well as solutions to problems that will be resolved.